DISTILASI AIR LAUT TENAGA SURYA DENGAN KONSENTRATOR LENSA FRESNEL - Eko Yudiyanto; Asrori . (Universitas Tridinanti Palembang, 2018)
Water supply is a basic need for life. Water management that requires a large amount of cost and energy is needed alternative solutions to produce a cheap process. Research on the distillation process was carried out to find solutions to these problems. The research was carried out by a experiment method to produce a distillation process for water purification.The experiment use an effective fresnel lens of 0.785 m2 and the receiver volume was 200 mL The results of the study explained that using a fresnel lens concentrator was able to generate steam. The steam can be condensed to produce fresh water. Data from calculation obtained average direct solar radiation is 531.98 Watts/m2 and the power received by the receiver is 346.61 Watt. The average normal solar radiation in tests is 515,7 W/m. The average temperature of the focus point on the cone receiver is 520,4OC.The wet steam generation process is obtained when the water temperature in the receiver shows 95OC. Experiments of distillation for 200mL sea water needed 10 minutes to reach 4 bar of pressure. Steam is flowed into the condenser so that distilled water is obtained 150 ml. Keywords: fresnel lens, solar destilation, drinking water